2024
DOI: 10.47197/retos.v53.101973
|View full text |Cite
|
Sign up to set email alerts
|

The Importance Of Archery Education Management In Physical Education Classes And Curriculum Programs For Students To Gain Skills In Many Areas

Hendra Setyawan Setyawan,
Sumaryanto Sumaryanto,
Suyanto Suyanto
et al.

Abstract: The research analyzes the urgency of implementing archery sports management as the development of 21st-century skill values ​​in schools. This research is mixed method research. Samples were taken by purposive sampling. Quantitative sample of 53 PE teachers. A qualitative sample of 30 people comprised 15 PE teachers, 5 archery athletes, 5 students, and 5 archery coaches/trainers. Quantitative data analysis uses descriptive statistics, while qualitative analysis uses data reduction, presentation, and conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Likewise, other research tried to associate general physical activities with concentration (Corona et al, 2019;Santamaría et al, 2018;Manzano et al, 2024;Valencia Sánchez et al, 2023). In addition, researchers also investigate sports class management and sports management Setyawan et al, 2024). Despite the burgeoning data, no research has discussed and tested the effectiveness of badminton-based Physical Education class management in increasing student concentration in elementary schools.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, other research tried to associate general physical activities with concentration (Corona et al, 2019;Santamaría et al, 2018;Manzano et al, 2024;Valencia Sánchez et al, 2023). In addition, researchers also investigate sports class management and sports management Setyawan et al, 2024). Despite the burgeoning data, no research has discussed and tested the effectiveness of badminton-based Physical Education class management in increasing student concentration in elementary schools.…”
Section: Introductionmentioning
confidence: 99%
“…In the Yogyakarta region of Indonesia, the potential for developing talented young athletes in archery is very large, however there are obstacles to elementary school students' interest in archery extracurricular activities, due to the lack of archery sports experts and the absence of archery sports facilities and infrastructure. Asresearch result (Setyawan et al, 2024) who recommend that PE teachers increase their competence in the field of archery and that schools provide the necessary facilities and infrastructure. Apart from that, research (Setyawan et al, 2023) also concluded that support for archery sports equipment is needed in schools or universities that hold archery sports classes, so that they can provide maximum achievement or learning results in archery skills for beginner archers.…”
Section: Introductionmentioning
confidence: 99%
“…Research related to archery has been done by several researchers, among others: (Barrera et al, 2020); (Roldan et al, 2021); (Wibowo et al, 2024); (Setyawan et al, 2024); (Yachsie et al, 2024). However, there has not been any research that discusses the implementing archery class management specifically designed for the pre-extracurricular program stage, in an effort to increase the interest of elementary school students in Yogyakarta in archery extracurricular activities.…”
Section: Introductionmentioning
confidence: 99%
“…Research related to physical education and sport has been conducted by many researchers, including (Hall-López, 2020); (Burgueño et al, 2021); (Botelho & Moreira, 2022); ; (Moya-Mata et al, 2023); ; (Meriño et al, 2024); (Setyawan et al, 2024). However, there is still very little research that discusses the differences in achievement in physical education learning outcomes for high school students based on parental occupation.…”
Section: Introductionmentioning
confidence: 99%